The Impact of Christian Religious Education on Generation Z Christian Nationalism Insight, with Spirituality as a Mediating Variable - Dhama Gustiar Baskoro; Dirk Roy Kolibu (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
The plurality of the Indonesian nation raises several important issues in the life of the Christian faith. Among the most important are the problems of religious syncretism with culture, pluralism, radicalism and intolerance. Of course, a multicultural diversity-based Christian Religious Education (CRE) curriculum is needed so that Christian spirituality can be translated well on the Indonesian context which adheres to Pancasila as an ideological view of nation and homeland, as well as diversity within unity. This research tries to test the relationship between the variables of Multicultural CRE (X), to dependent variable (Y) Christian Nationalism Insight, with the variable spirituality (Z) as the moderator variable. Data analysis was conducted using Structural Equation Modelling-Partial Least Square (SEM-PLS) using SmartPLS software version 3, with a small sample of 40 students participating in the Multicultural CRE course. The results explain that there is a significant effect between Multicultural CRE and Christian Nationalism Insight, also significant effect of Multicultural CRE to Spirituality, but the result is not show spirituality as a mediating variable has significant effect to Christian Nationalism Insight. This result show, the magnitude of the contribution of CRE to develop Spirituality and Christian Nationalism Insight.